The Effect of Septage Sludge and Oxidizing Agents in the Microbial Fuel Cells Generating Electricity - Safitri, Vidia Wahyu Meidy; Yuniarto, Adhi; Purnomo, Alfan; Marhendra, Bara Awanda (Tecno Scientifica Publishing, 2023)
Earlier research demonstrated the efficacy of microbial fuel cells in both wastewater treatment and renewable electric current generation. In this process, microbial fuel cells harness the potential of wastewater as a substrate and energy source, enabling microorganisms to generate electric current. Introducing microorganisms sourced from septage sludge acts as a microbial catalyst. Additionally, tofu wastewater is employed as a nutritional resource to support the growth of these microorganisms. A dual-chamber reactor was utilized to carry out this study, featuring an anode and a cathode connected through a salt bridge. Various substrate variations were performed on the anode, specifically with a combination of tofu liquid waste and septage sludge at ratios of 1:1, 1:2, and 1:3. Additionally, different electrolyte solutions, such as KMnO4 and K3(Fe(CN)6), were used at the cathode. Using different electrolyte solutions as electron acceptors can enhance the electric current production generated. The study spanned 240 hours of operation, during which electric current, voltage, COD, and BOD measurements were taken at 48-hour intervals. The findings revealed that including septage sludge in a 1:3 ratio yielded the highest current strength compared to other substrate variations, measuring 16.34 mA. When using a 0.25 M KMnO4 as an electrolyte solution, the voltage recorded was 8.78 V. Additionally, the most effective removal of COD and BOD content was achieved with a substrate ratio of 1:3 in the presence of KMnO4, achieving removal rates of 95.12% and 96.45%, respectively. These results indicate that adding septage sludge contributes to increased electricity current production.